Pattern of Cancer in Nepal from 2003 to 2011 - Sah, Sunil Kumar; Yadav, Naval Kishor; Kurmi, Roshan; Rauniyar, Ramanuj; Manandhar, Krishan Das; Gupta, Birendra Prasad (Nepal Journal of Biotechnology, 2016)
Correction: On 15th January 2017, the authors Sunil Kumar Sah and Naval Kishor Yadav were added to the author list.Cancer is global burden of disease in developed and developing countries. It is one of the main causes of death. The environmental factor and life styles are major causes of cancer.This hospital based retrospective study was carried out using data retrieved from the register maintained at seven cancer centers. The most common basis of diagnosis were microscopic (histopathological and cytopathological examination). The diagnosis was also based on clinical examination, radiological examination, endoscopy, biochemical and immunological tests.Most of the cancer cases were diagnosed at BPKMCH (23908) followed by BPKIHS (9668) and BH (5959) and few cases from KCH (518) in 2003 to 2011. The total number of cancer cases were increasing from 2003 to 2011 and it become double in 2011. Out of 75 district of Nepal, more number of cancer cases was found in Kathmandu, Sunsari, Morang, Chitwan, Lalitpur, Jhapa, Kaski, Nawalparasi, Rupendehi and Kavrepalchowk in 2010. Similarly, in 2011 more number of cancer cases was found in Kathmandu, Morang, Jhapa, Sunsari, Chitwan, Lalitpur, Rupendehi, Kaski, Saptari, Bhaktapur. Lung cancer was the common cancer and similarly, other prevalent cancers were cervical, breast, stomach, ovarian and colo-rectum cancer in 2003 to 2011. The common cancers were lung, cervical, breast, stomach, ovarian and colo-rectum. The number of patients is increasing, which may be due to change in life style and lack of education.